2017
DOI: 10.7554/elife.29428
|View full text |Cite
|
Sign up to set email alerts
|

AMPylation targets the rate-limiting step of BiP’s ATPase cycle for its functional inactivation

Abstract: The endoplasmic reticulum (ER)-localized Hsp70 chaperone BiP contributes to protein folding homeostasis by engaging unfolded client proteins in a process that is tightly coupled to ATP binding and hydrolysis. The inverse correlation between BiP AMPylation and the burden of unfolded ER proteins suggests a post-translational mechanism for adjusting BiP’s activity to changing levels of ER stress, but the underlying molecular details are unexplored. We present biochemical and crystallographic studies indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 61 publications
(104 reference statements)
7
107
0
4
Order By: Relevance
“…Increasing its concentration by overexpression favours FICD dimerisation and thus perturbs such regulatory transitions. This could account for the observation that FICD overexpression, in unstressed wild‐type cells, abolishes the small pool of BiP‐AMP normally observed under basal conditions (Preissler et al , ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Increasing its concentration by overexpression favours FICD dimerisation and thus perturbs such regulatory transitions. This could account for the observation that FICD overexpression, in unstressed wild‐type cells, abolishes the small pool of BiP‐AMP normally observed under basal conditions (Preissler et al , ).…”
Section: Resultsmentioning
confidence: 97%
“…Consequently, BiP-AMP has high rates of client protein dissociation (Preissler et al, 2015b). Moreover, the ATPase activity of BiP-AMP is resistant to stimulation by J-domain protein co-factors, which greatly reduces the chaperone's ability to form high-affinity complexes with its substrates (Preissler et al, 2017b). AMPylation therefore serves to inactivate BiP.…”
Section: Introductionmentioning
confidence: 99%
“…Also, substantially obscure remains the relevance of post-translational cellular responses to intra-compartmental load with misfolded proteins. These poorly characterized events consists in regulated covalent modification that modulate chaperone activities (e.g., ampylation of BiP (60,61) or calnexin palmitoylation (62)), regulated formation/disassembly of functional complexes or regulated turnover of specific ER-resident factors that control, for example, degradation of misfolded proteins (ERAD tuning) (57,63,64). As a final note on this subject, although comparison of transcriptomics and proteomics nicely revealed the transcriptional nature of the UPR, our LFQ-MS analyses additionally identified a number of proteins, whose level is enhanced on ER load with unfolded BACE457, BACE457∆ and CD3δQQQ in the absence of transcriptional induction of the corresponding genes.…”
Section: Discussionmentioning
confidence: 99%
“…One known substrate of FICD is HSPA5, which is a chaperone located in the endoplasmic reticulum (ER) and master regulator of the unfolded protein response (UPR) [3][4][5][6] . Recent data show that FICD regulates the ATPase activity of HSPA5 and its interactions with unfolded proteins, but the exact function is not yet clear 13 . However, it was found that the HSPA5 AMPylation associates with changes in neuronal fitness in drosophila 3, [14][15][16] .…”
mentioning
confidence: 99%